Ranking by rating - Yves Sprumont (Theoretical Economics, 2018)
Ranking by rating consists in evaluating the performances of items using exogenous rating functions and ranking these items according to their performance ratings. Any such method is separable: the ordering of two items does not depend on the performances of the remaining items. When performances belong to a finite set, ranking by rating is characterized by separability and a property of consistency; this characterization generalizes to the infinite case under a continuity axiom. Consistency follows from separability and symmetry or from monotonicity alone. When performances are vectors in R m + , a separable, symmetric, monotonic, continuous, and invariant method must rank items according to a weighted geometric mean of their performances along the m dimensions.
Keywords: D71; D89; 330; Ranking methods; separability